Evaluation of oscillometric blood pressure measurement devices available for online sale - Estefanie Siqueira Vigato; Mariana Castro de Souza; Priscila Rangel Dordetto; José Luiz Tatagiba Lamas (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to characterize oscillometric blood pressure measurement devices for sale in the virtual market and identify which ones have undergone a validation study. Methods: this was a cross sectional study. The search for devices for sale was conducted on websites, and the sample was composed of 137 devices obtained from 644 ads. We conducted a bibliographic survey in five databases and web pages enlisting devices submitted for validation. The Kolmogorov-Smirnov test was used to check data distribution, followed by Mann-Whitney and Kruskal-Wallis tests for comparisons, using the SAS 9.4 program. Results: only 16.7% of the devices were validated. The home devices ranged from USD 10.57 to USD 275.67. Only 102 ads informed the cuff size, with different nomenclatures. Conclusions: most ads contained non-validated devices, which were cheaper. We identified some ads falsely informing validation.